Modeling and Forecasting of Total Supply Malaysia’s Centrifugal Sugar Using ARIMA Model - Shafie, Nur Amalina; Borhan, Nurbaizura; Ariffin, Noor Amalina Nisa; Isa, Khairil Anuar Md; Ghani, Nor Azura Md (Advances in Social Sciences Research Journal, 2024)
Centrifugal sugar is essential to Malaysia's food sector and culinary scene because it is high-quality, consistent, and convenient for a variety of food and beverage applications. Customers, chefs, and food manufacturers who are looking for dependable sweetening solutions for their regular cooking and dining experiences choose it because of its broad availability and adaptability. To support market stability, price control, production scheduling, trade policy development, risk management, policy formation, and consumer welfare, it is essential to forecast the centrifugal sugar supply in Malaysia. Autoregressive Integrated Moving Average (ARIMA) model is one of Box-Jenkins model which is common time series forecasting methodology that is widely utilised in various sectors including economics, finance, and business. Therefore, this research interest to model and forecast the total supply of centrifugal sugar in Malaysia using ARIMA model. This research used data from the IndexMundi website and analysed by using R software. This research found that the best model to forecast the total supply Malaysia’s centrifugal sugar is ARIMA (1,1,2). The total supply of Malaysia’s centrifugal sugar will increase in 6 years ahead.